A Pushed Descending Aorta due to Hiatal Hernia - Gecmen, Cetin; Kahyaoglu, Muzaffer; Kalayci, Arzu; Cakmak, Ender Ozgun; Candan, Ozkan; Guner, Ahmet; Izgi, Ibrahim Akin; Kirma, Cevat (AORTA, 2018)
A 91-year-old female patient was admitted to hospital for evaluation of transcatheter aortic valve implantation. A chest radiography showed a hiatal hernia, and the stomach and duodenum appeared in the thoracic cavity. The descending aorta was pushed by the stomach and duodenum.
Keywords: descending aorta; aortic displacement; hiatal hernia